Tokoh dan Penokohan dalam Naskah Drama Kinanti Si Penakluk Mimpi Karya Nataya Bagya - Muhammad - Thaariq (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2023)
The results obtained were in the form of descriptions of the drama manuscript analysis Kinanti Si Penakluk Mimpi by Nataya Bagya. This study examined about figures and management in a text using an objective approach method that is descriptive and its research results in the form of a role and character or character of each character in the text. The data collection techniques used by researchers is to read, record and analyze selectively. The source of data in this study is one of the manuscripts in books Bayang(K)an.